2016
DOI: 10.5194/nhess-2016-297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liquefaction, landslide and slope stability analyses of soils: a case study of soils from part of Kwara, Kogi and Anambra states of Nigeria

Abstract: 11Landslide is one of the most ravaging natural disaster in the world and recent occurrences in Nat. Hazards Earth Syst. Sci. Discuss., doi:10.5194/nhess-2016Discuss., doi:10.5194/nhess- -297, 2016 Manuscript under review for journal Nat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…The result implies that root matric has significant effect on cohesion and this effect varies with the depth depending on root length density. It has been reported that soil strength increases with depth due to the increase in interaction between root and soil particles [30,40,67,68]. In the present study, plants roots has greatest effect at shallow depth of slope than deeper, where the root length density is generally the highest.…”
Section: Influence Of Root Penetration Depth On Factor Of Safetysupporting
confidence: 46%
See 2 more Smart Citations
“…The result implies that root matric has significant effect on cohesion and this effect varies with the depth depending on root length density. It has been reported that soil strength increases with depth due to the increase in interaction between root and soil particles [30,40,67,68]. In the present study, plants roots has greatest effect at shallow depth of slope than deeper, where the root length density is generally the highest.…”
Section: Influence Of Root Penetration Depth On Factor Of Safetysupporting
confidence: 46%
“…The safety factor of the vegetated slope increases with decreasing vegetation spacing. Plants vegetated on entire slope surface with smaller vegetation spacing increase root density and enhanced interlink of thin roots for soil reinforcement as depicted by [2,12,33,40,69]. The result from the analysis shows that as the spacing of vegetation increases, enhancement of soil shear strength of the slope decrease and the slope is prone to failure.…”
Section: Effect Of Vegetation Spacing To Safety Factor Of Slopementioning
confidence: 98%
See 1 more Smart Citation
“…Globally, natural disasters have become a great challenge to humans. These disasters ranged from the failures of embankments, natural slopes, earth structures and foundations; and they have been attributed to the liquefaction of sands, landslides and slope instability (Ige et al, 2016). However, these natural disasters are a result of seismic effects and only occur in a geographical area with distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This may cause huge decrease in the cohesion and angle of internal friction which can lead to slope instability [4]. A group of researchers added that the liquefaction rate for soil mainly composed of sand and silt are higher compared to that with clay [5]. The liquefaction is also greatly influenced by the low plasticity soil.…”
Section: Introductionmentioning
confidence: 99%